The psychology of science text comprehension - Otero, José; León, José A.; Graesser, Arthur C. (L. Erlbaum Associates, 2002)
This volumes presents contemporay research and theories of scientific text comprehension. The enterprise of textbook design needs to be effectively integrated with research in discourse processing, educational technology and cognitive science. This book promotes such an integration.